Pemanfaatan Platform Digital dalam Pemasaran Produk Perikanan dan Kelautan - Dita Indra Febryanti; Diana Ari Utami (Jurnal Green Growth dan Manajemen Lingkungan, 2023)
Fisheries and marine products are major contributors to Indonesia's maritime economy, but their contribution to GDP and the welfare of coastal communities is still low. Fishermen as the main actor in this industry have limitations in terms of technology and marketing of their products. The presence of information technology in the marketing of fishery products is an urgency for improving fishermen's welfare. Aruna Indonesia is a startup that connects fishermen as individuals and cooperatives with end buyers through the use of Information Technology (IT). Fishermen place their products on the Aruna Indonesia website so that end buyers can order products online. The establishment of Aruna Indonesia is seen as a solution to the distribution chain problems for fishery and marine products. The purpose of this study is to analyze the empowerment of fishermen as Aruna Indonesia's partners in marketing fishery and marine products and to analyze how significant the use of digital platforms to the marketing of fishery and marine products to support fishermen's welfare. This study used a qualitative method with a case study approach and data collection was carried out through interviews and literature study with the research subjects of the Aruna Indonesia team and fishermen as Aruna’s partners. The use of digital platforms can simplify and enlarge the marketing of fisheries and marine products by empowerment carried out by Aruna Indonesia and improve the welfare of fishermen as well.